2012
DOI: 10.1021/jp300037r
|View full text |Cite
|
Sign up to set email alerts
|

L10 Ordering of Ultrasmall FePt Nanoparticles Revealed by TEM In Situ Annealing

Abstract: The transformation of ≤4 nm equiatomic FePt nanoparticles from the disordered cubic A1 to the ordered tetragonal L1 0 phase was studied by means of high-resolution transmission electron microscopy coupled with in situ heating experiments. In accordance with ex situ annealing experiments, a transition temperature of around 500°C was determined. Diffusion is enhanced at surfaces and plays a dominant role in the ordering process. Hence, the ordering of the crystallographic structure starts at the surface of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 21 publications
5
40
0
Order By: Relevance
“…Catalysts design for the oxygen reduction reaction (ORR) in a proton‐exchange membrane fuel cell (PEMFC), in particular, is an area that has received momentous thrust as an effect. The principal findings of this research effort provide much expansive insight into the fundamental understanding of nanoscale materials . Although platinum (Pt) is known to exhibit exceptional activity towards the sluggish ORR kinetics, it still remains an economically nonviable option for large‐scale implementation of PEMFC, owing to its depleting natural sources and exceedingly high costs .…”
Section: Resultsmentioning
confidence: 99%
“…Catalysts design for the oxygen reduction reaction (ORR) in a proton‐exchange membrane fuel cell (PEMFC), in particular, is an area that has received momentous thrust as an effect. The principal findings of this research effort provide much expansive insight into the fundamental understanding of nanoscale materials . Although platinum (Pt) is known to exhibit exceptional activity towards the sluggish ORR kinetics, it still remains an economically nonviable option for large‐scale implementation of PEMFC, owing to its depleting natural sources and exceedingly high costs .…”
Section: Resultsmentioning
confidence: 99%
“…Delalande et al reported [35] that heating a nanoparticle with 2nm radius at 670 K for 24 min and subsequently at 770 K for 1 min yielded a single ordered domain roughly 50% of the particle size. Because the particle has been pretreated for an extensive period of time at 673 K, when annealing at 770 K it probably had readily formed nuclei.…”
Section: Resultsmentioning
confidence: 99%
“…Particles annealed on the right side of the curve are transformable in theory while those annealed on the left side are not. Clearly, all the ultra-small FePt nanoparticles' reported transformability, [20,35,[48][49][50] In our previous thermodynamic studies [36], to address the influence of particle morphology on order-disorder transition, we introduced a shape factor "α" into our equation as a convenient way to account for the additional surface areas created by the presence of polyhedral shapes. The factor "α" is defined as the surface area ratio between non-spherical and spherical nanoparticles of identical volumes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, understanding the effect of the support on TEM imaging of catalyst systems is necessary to accurately distinguish such imaging artifacts from actual structural evolution occurring in supported nanoparticles under environmental conditions. In situ TEM, which enables the observation of structural changes under environments -e.g., temperature, gaseous atmosphere, liquid -approaching those of working conditions [19][20][21][22][23], faces additional imaging challenges, as the presence of liquid, gas, and/or windows from closed-cell holders can greatly reduce signal intensity.…”
Section: Introductionmentioning
confidence: 99%